Cash Flow Statement Analysis of PT Astra Agro Lestari Tbk. Jakarta - Wendy Teguh Putri Zega; Mangasa Sinurat; Dame Ria Rananta Saragih (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2026)
Cash flow fluctuations in companies can indicate financial instability, making it essential to analyze whether cash is generated from sustainable operations or external financing. The study investigates PT Astra Agro Lestari Tbk cash flow statement performance from 2022 to 2024 while evaluating the company's capacity to generate operating cash flows and finance its investments and fulfill its funding needs. The research question in this study is how the company's cash flow performance is reviewed from cash flow ratios and common size analysis in operating, investing, and financing activities. The research method employed in this study uses quantitative descriptive research to analyze secondary data which includes cash flow statements obtained from the Indonesia Stock Exchange. The analysis technique used operating cash flow ratio calculation and current liability cash coverage ratio calculation and capital expenditure ratio calculation and total debt ratio calculation and common size analysis to determine cash flow component proportions. The results indicate that operating cash flow showed variable performance throughout the period yet reached its highest point which resulted in increased company liquidity. Companies spent most of their investment funds on fixed assets and biological assets while their financing activities depended on bank loans. The study results emphasize that companies need to achieve operational efficiency through better investment planning and funding structure control to achieve long term financial stability.